Determinan Kecenderungan Kecurangan (fraud) Akuntansi Pada Koperasi Se Kecamatan Selong - Gayatri, Baiq Alon Pramudhya; Isnaini, Zuhrotul (Universitas Hamzanwadi, 2024)
This research aims to analyze the determinants of accounting fraud tendencies consisting of suitability of compensation, information asymmetry, organizational commitment and individual morality in cooperatives throughout Selong District. This research was conducted at cooperatives in Selong District, totaling 25 cooperatives. This research sample was taken using a purposive sampling technique and used a questionnaire method which was distributed to 75 respondents. The data analysis technique uses multiple linear regression analysis with SPSS version 24 application. The results of the research show that individual morality has a negative effect on the tendency to cheat. Meanwhile, suitability of compensation, information asymmetry and organizational commitment have no effect on the tendency to cheat. This research can be a reference for cooperatives in efforts to prevent fraud.